2020
DOI: 10.1093/ehjci/jeaa324
|View full text |Cite
|
Sign up to set email alerts
|

Mitral annulus disjunction is associated with adverse outcome in Marfan and Loeys–Dietz syndromes

Abstract: Aims We aimed to assess the prevalence of mitral annulus disjunction (MAD) and to explore the association with aortic disease and mitral valve surgery in patients with Marfan syndrome (MFS) and Loeys–Dietz syndrome (LDS). Methods and results We included consecutive MFS patients fulfilling Revised Ghent Criteria and LDS patients fulfilling Loeys–Dietz Revised Nosology. MAD was identified by echocardiography and was quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
3
19
2
1
Order By: Relevance
“…In studies with serial follow-up, rates of aortic root dilation ranged from 0.11-0.67 cm/year (13,20,29), with children with LDS type 2 demonstrating the greatest progression of aortic root dilation compared to LDS type 1 and 4 (30). Several studies have also identified a correlation between the presence of craniofacial features (13,14), carotid artery tortuosity (31), vertebral artery tortuosity (32), aortic arch geometry (33), aortic stiffness (34), and mitral annular disjunction (35) with increased aortic risk. Aortic root dilation in children should lead to the suspicion of connective tissues disorders, including LDS.…”
Section: Cardiovascular Involvementmentioning
confidence: 99%
“…In studies with serial follow-up, rates of aortic root dilation ranged from 0.11-0.67 cm/year (13,20,29), with children with LDS type 2 demonstrating the greatest progression of aortic root dilation compared to LDS type 1 and 4 (30). Several studies have also identified a correlation between the presence of craniofacial features (13,14), carotid artery tortuosity (31), vertebral artery tortuosity (32), aortic arch geometry (33), aortic stiffness (34), and mitral annular disjunction (35) with increased aortic risk. Aortic root dilation in children should lead to the suspicion of connective tissues disorders, including LDS.…”
Section: Cardiovascular Involvementmentioning
confidence: 99%
“…The first diagnosed MAD in 41% of 168 patients with either Marfan syndrome or Loeys-Dietz and found that MAD was associated with more mitral valve surgery and younger age at aortic dissection or prophylactic surgical repair. 56 Another recent article reported that 34% of 142 patients with Marfan syndrome had MAD as diagnosed by TTE. 57 Patients with MAD had larger aortic root z scores and more MVP, ventricular ectopy, and NSVT.…”
Section: Mad In Special Populationsmentioning
confidence: 99%
“…(4) Up to 40% of patients with MFS and Loeys-Dietz syndrome demonstrate echocardiographic evidence of MAD, which was associated with aortic events at a younger age and a greater need for mitral surgery. Furthermore, MAD was more common in patients with documented VA. (5) With emerging clinical experience linking MAD and MVP to a risk of SCD, this case series highlights three patients who present with features of malignant MVP and MAD with underlying HAD. It is unclear whether this highlights a unique disease entity with a common pathophysiologic substrate, represents unique patients with overlap syndromes, or introduces MAD as an arrhythmogenic risk marker in aortopathy syndromes.…”
Section: Discussionmentioning
confidence: 92%
“… 4 Up to 40% of patients with MFS and Loeys–Dietz syndrome demonstrate echocardiographic evidence of MAD, which is associated with aortic events at a younger age and a greater need for mitral surgery. Furthermore, MAD is more common in patients with documented VA. 5 …”
Section: Discussionmentioning
confidence: 99%